PERAN KEPUASAN KERJA MEMEDIASI PENGARUH STRES KERJA TERHADAP TURNOVER INTENTION PERAWAT RSUD TABANAN - Antara, I Made Oko Dwi; Surya, Ida Bagus Ketut; Suwandana, I Gusti Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.02.TAHUN.2024DO - 10.24843/EEB.2024.v13.i02.p18, 2024)
This study aims to analyze the role of job satisfaction in mediating the effect of work stress on nurse turnover intention at the Tabanan Regional General Hospital. This study used a sample of 188 non-Civil Servant nurses using the saturated sampling method. The method used in data collection is a survey method with the instrument used is a questionnaire. The data that has been collected is then analyzed using a Partial Least Square (PLS) based Structural Equation Modeling (SEM) inferential statistical analysis tool. The results showed that work stress had a positive and significant effect on turnover intention. Job stress has a negative and significant effect on job satisfaction. Job satisfaction has a negative and significant effect on turnover intention, and job satisfaction partially mediates the complementary effect of work stress on turnover intention.